Maybank Investment Banking Group / Stephnie Tony - Tony, Stephnie (Faculty of Business and Management, 2025)
This report primarily outlines my internship experience with Maybank Investment Banking Group (MIBG), which began on 29th July 2024 and ended on 10th January 2025. My main objective when I started the internship was and still is to gain and expand my knowledge of the banking sector in Malaysia, finance, and investments. However, my key focus was to deepen my understanding of digital broking, as this was a central aspect of my role at MIBG during the internship. A notable aspect of MIBG that I recently discovered is their strong emphasis on upcoming digital platform projects. I am proud to have had the opportunity to contribute to and be involved in these significant initiatives, particularly in supporting the progress of these projects. Many of us are likely familiar with the MAE by Maybank2U app, which was launched back in August 2020. Through this initiative, Maybank introduced its mobile banking and e-wallet services to enhance customer experience and accessibility. Similar to MAE application, I worked with my project team on improving and transforming the MIBG existing product, which is the Maybank Trade app to make it more competitive in the market. All in all, this internship was not just about fulfilling course requirements; but it also sparked my interest in investment banking, not only in Malaysia but across Southeast Asia.